The Moslem women between west and Islam (Journal of the College of Education for Women, 2019)
The Moslem women between west and Islam ,This study deals with Muslim womenfrom the west Pont of view in the oriental studies or the western media and how it wasexposed to ill-treatment or evil-eyed by the west due to misunderstanding or it was done onpurpose that they didn’t comprehend how the women deals with Islam ,so this western viewassured that Islam had disparaged the women's position and hindered her freedom, aiming atstabbing Islam and dislocate the Islamic tissue which is formed from man and women.This study has established with evidences the distance of this western view from realityIslam in fact raised and lifted women's position while the western women was living onthe margin of life, robbed from most of her rights for long centuries.This study also deals with this matter through three axes, the first axis is related with theoriental studies, the second axis is related with western media, the third one is found in Islam,it focuses on the problem of numerical or numerous wives, and on the injustice rights betweenman .Finally, this study reached to appoint that Islam, is one of the most religions of the wordhas freedom and liberty in the matter of women. It is the only play ground through whichwomen can established her being and personality without causing any harm to herdignity,honour and humanty,On what is really happening to western women, who has been robbed from her rights on account of equality or being equal with the other sex>